Raton Telephone Directory (Raton, NM Coda Publications, 2006)
First published by Mountain States Telephone & Telegraph Company, This reproduction of the 1952 Raton phone directory was done by William Carroll in 2006. A fascinating picture of the city at the time.
Keywords: Raton, NM -- telephone directories; Mountain States Telephone & Telegraph Company -- telephone directory